Degree of physician-pharmacist collaboration and influencing factors in a teaching specialized hospital in Ethiopia. Issue 3 (4th May 2021) - Nasir, Beshir Bedru; Gezahegn, Getahun Tigistie; Muhammed, Oumer Sada
ABSTRACT: Several studies have found that physician-pharmacist collaboration improves medication therapy outcomes. This study aimed to measure the degree of physician-pharmacist collaboration in Ethiopia, to identify associated factors, and to determine barriers to their collaboration. A cross-sectional study was conducted among 299 health professionals (246 physicians and 53 pharmacists) in Tikur Anbessa Specialized Hospital, Ethiopia. The Collaborative Working Relationship Model and the Physician–Pharmacist Collaborative Instrument (PPCI) with three main exchange characteristics (trustworthiness, role specification, and relationship initiation), and collaborative care items were used. Barriers to collaboration and areas that need further collaboration were assessed. Multiple regression was used to assess influencing factors. This study revealed that, in Ethiopia, physicians had higher PPCI mean scores on collaborative care items (4.22 ± 1.35) compared to pharmacists (3.25 ± 0.86). Areas of practice and relationship initiation were the two influencing factors for collaboration among pharmacists. But for physicians, age, areas of practice, educational qualification, role specification, and trustworthiness were the factors associated with collaboration. Lack of face-to-face communication and fragmentation of care were the common barriers. However, the vast majority of members of both professions believed that collaboration should be developed in their future practice. Their current collaboration seems suboptimal, and exchange characteristics, which reflect interactions between the practitioners, had a significant influence on their collaboration in addition to other factors.